Combined Energy-oriented Path following and Collision Avoidance approach for Autonomous Electric Vehicles via Nonlinear Model Predictive Control - Bifulco, Gennaro Nicola; Coppola, Angelo; Loizou, Savvas; Petrillo, Alberto; Santini, Stefania (My University, 2021)
This paper addresses the problem of computing an eco-driving speed profile for an autonomous electric vehicle traveling along curvy roads while ensuring path following/car following functionalities w.r.t. possible preceding vehicles ahead. To solve it, we propose a double-layer control architecture combining the classical Adaptive Cruise Control with a Nonlinear Model Predictive Control. This latter is designed so to drive the autonomous vehicle along a predefined path while guaranteeing the maintenance of a safe distance w.r.t. a predecessor vehicle ahead and ensuring energy-saving consumption. The appraised control-oriented design model is non-linear and the energy consumption one explicitly accounts for the cornering effects. Numerical results confirm the effectiveness of the proposed control architecture and disclose its ability in guaranteeing energy saving.
Keywords: Autonomous Vehicle; Eco-Driving; Electric Vehicle; Model Predictive Control; Path Following